A fast and reliable LC-MS-MS method for the quantification of saxitoxin in blood plasma samples - Odehnalová, Klára; Přibilová, Petra; Maršálek, Blahoslav; Babica, Pavel (Journal of analytical toxicology, 2024)
Saxitoxins (STXs) are potent neurotoxins produced by marine dinoflagellates or freshwater cyanobacteria known to cause acute and eventually fatal human intoxications, which are classified as paralytic shellfish poisonings (PSPs). Rapid analysis of STXs in blood plasma can be used for a timely diagnosis and confirmation of PSPs. We developed a fast and simple method of STX extraction based on plasma sample acidification and precipitation by acetonitrile, followed by quantification using liquid chromatography-tandem mass spectrometry (LC-MS-MS). Our approach provides the results ≤30 min, with a limit of detection of 2.8 ng/mL and a lower limit of quantification of 5.0 ng/mL. Within-run and between-run precision experiments showed good reproducibility with ≤15% values. Standard curves for calibration were linear with correlation coefficients ≥0.98 across the assay calibration range (5-200 ng/mL). In an interlaboratory analytical exercise, the method was found to be 100% accurate in determining the presence or absence of STX in human plasma specimens, with recovery values of 86-99%. This simple method for STX determination in animal or human plasma can quickly and reliably diagnose STX exposures and confirm suspected PSP cases to facilitate patient treatment or expedite necessary public health or security actions.
Keywords: Saxitoxin; Animals; saxitoxin; Humans; Tandem Mass Spectrometry; Reproducibility of Results; Plasma; Chromatography, Liquid; Liquid Chromatography-Mass Spectrometry; lidé; reprodukovatelnost výsledků; krevní plazma; kapalinová chromatografie-hmotnostní spektrometrie; tandemová hmotnostní spektrometrie; chromatografie kapalinová; zvířata